Infographics - Allen, WL; Amit-Danhi, ER (Edward Elgar Publishing, 2024)
Infographics—or visuals designed to convey information efficiently, coherently, and comprehensibly—are important ways by which different actors communicate to achieve their objectives. This entry introduces the main conceptual, theoretical, and empirical avenues of research on infographics in political domains, with particular emphasis on issues arising from their use in digital contexts. First, we locate infographics within the larger field of visual political communication, and then distinguish them from the related mode of data visualization. Then, we identify major lines of research into the forms, production, consumption, political impacts, circulation patterns, and veracity of infographics. Finally, we highlight how questions of power run through political examinations of infographics, and illustrate this with reference to the domains of categorization, elections and campaigning, policymaking, and social movements.